Good Corporate Governance Toward Financial Performance Of Islamic Bank In Indonesia - Diana, Nur; Syafi’i, Imam; Maulidiyah, Nailin Nikmatul (JPS (Jurnal Perbankan Syariah), 2024)
This research aims to analyze the influence of good corporate governance (GCG) on the financial performance of Islamic banks in Indonesia. This study uses a quantitative approach. The population in this research is 16 Islamic banks registered with the Financial Services Authority (FSA) for the 2021-2022 period. The sample used was 10 Islamic banks that issued quarterly report data. Sample selection was carried out using the purposive sampling method. The data collection technique uses secondary data in Islamic bank documentation and is processed using the SPSS 25 application with multiple linear regression tests. The results of this research are that the board of commissioners has a negative effect on the financial performance of Islamic banks, and the board of directors has a positive effect on the financial performance of Islamic banks. In contrast, the Sharia supervisory board does not affect the financial performance of Islamic banks. Theoretical research can complement existing theories and be a reference for future research. This research can be a reference for Islamic banking in analyzing corporate governance standards to provide investors with more knowledge and understanding about the financial performance of Islamic banking and enable investors to make the right decisions.